CAMPUR KODE DALAM PROGRAM ACARA TV BREAKOUT OLEH BOY WILLIAM - Rarobong, Fangky Agusta Imanuel; Pelealu, Hetty; Manus, Jeane Angela (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â ABSTRACTThe research is entitled â€œCode Mixing in the tv Show Program â€˜Breakoutâ€™ by Boy Williamâ€. It is an Attempt to analyze and explain the mixing code analysis` in Host on Breakout. The objective of this research is to identify, classify, and analyze the Code Mixing in the TV show program Breakout by Boy William. The writer conducts this research by using descriptive method. In collecting data, videos were taken from youtube as a source of data. In analyzi data, the writer used theory by Hoffman (1991:116). The theory consists of ten reasons, they are: Talking about particular topic, Quoting somebody else, Being emphaty something (express solidarity), Interjection (interesting sentence fillers or sentence connectors), repetition used for clarification, Intention of clarifying, The speech content for interlocutor, Expressing group identity, To soften or strengthen request or command, Because of real lexical need, to exclude other people when a comment is intended for only a limited audience. The results of this research indicate that in code mixing there are 60 reasons for the sentances used by the presenter on the Breakout tv program according to Hoffman's theory (1991: 116).Keywords: Sociolinguistic, Mixing Code, Breakout (Music Television).